Oxford school atlas - Wiegand, Patrick (Oxford University Press Karachi, 2006)
Featuring easy-to-read digital maps, this atlas uses satellite images, photographs and artwork to enhance the themes chosen. The level of detail is accessible to 10+ geographers and the topics are specifically chosen to cover the key curriculum requirements.